Finding a solution for the tradeoff between time, cost and sustainability/LEED credits for new construction - Kumar, Shantanu, author; Mehany, Mohammed S. Hashem M., advisor; Guggemos, Angela Acree, committee member; Anderson, Charles W., committee member (Colorado State University. Libraries, 2018)
Project complexity generated tradeoffs in construction, which evolved over decades. This research focuses on the tradeoff between time-cost and sustainability represented in the LEED credits (Materials and Resources in particular). The research was broken down into preliminary and validation studies, wherein the preliminary study used an exhaustive search to find the optimized solution. In validation case study, the size of dataset increased exponentially, and it became computationally incompatible to find the optimized solution. Genetic Algorithm (GA) was hence used to find the optimized solution based on priority factors entered by the user. Usage of GA was validated using the preliminary study data and then applied to the validation study data. A tradeoff could be seen between the priority factors and the optimized solution. It was found that the optimization model was successful in minimizing the time and cost, concurrently maximizing the credits for a validation case study conducted for a real-life project.
Keywords: genetic algorithm; optimization; tradeoffs; LEED; construction; sustainability